COVID-19 infection in pregnant women, preterm delivery, birth weight, and vertical transmission: a systematic review and meta-analysis - Géssyca Cavalcante de Melo; Karina Conceição Gomes Machado de Araújo
In less than four months, the total of confirmed cases of COVID-19 was 1,684,833 worldwide. Outcomes among the public of pregnant women with COVID-19 are still unclear. We performed a systematic review and meta-analysis to analyze whether COVID-19 in pregnant women is related to premature birth and birth weight, and to summarize the diagnostic results of neonates born to mothers with COVID-19 for investigating the possibility of vertical transmission. Searches were performed in PubMed, Scopus, LILACS, Web of Science, Google Scholar, Preprints, bioRxiv, and medRxiv. We used the odds ratio (OR) and mean difference (MD) as measure of analysis. Summary estimates were calculated using random effects models. 38 studies were included; data from 279 women were analyzed; 60 patients were diagnosed with COVID-19. The meta-analysis showed no significant association between COVID-19 and preterm delivery (OR = 2.25; 95%CI: 0.96, 5.31; p = 0.06; I² = 0%). No significant relationship was found between birth weight and COVID-19 (MD = -124.16; 95%CI: -260.54, 12.22; p = 0.07; I² = 0%). Among 432 newborns, 10 were reported with positive results for early SARS-CoV-2. Due to the characteristics of the studies, the level of evidence of this meta-analysis was considered very low. COVID-19 in pregnant women may not be associated with the occurrence of preterm deliveries or the birth weight of the newborn children, however the evidence to date is very uncertain. A few reports suggest vertical transmission of SARS-CoV-2 to newborn is possible, but evidence is still uncertain.